THE RELATIONSHIP BETWEEN ORGANIZATIONAL CLIMATE AND WORK MOTIVATION TO ORGANIZATIONAL COMMITMENT IN PT. CITRA ABADI ABADI - Berti Anggun Melati; Anoesyirwan Moeins; Martinus Tukiran (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The purpose of this study was to examine the strengths of the relationship between organizational climate and work motivation and commitment to organization in PT. True Eternal Image. The study population was the operator of PT. Citra Abadi Sejati as many as 454 operators with a sample size of 213 operators calculated using the Slovin formula with an error rate of 5%. Collecting data for each variable studied using a questionnaire with a rating scale. The data analysis technique used descriptive statistical analysis techniques and inferential statistical analysis techniques. The results showed: (a) There is a significant positive relationship between Organizational Climate and Commitment to Organization with a correlation coefficient of ry.1 = 0.579, the strength of the relationship is "moderate". The amount of contribution of organizational climate to commitment to the organization is 33.5% and the regression equation ? = 51.182 + 0.576X1. This means that the Commitment to the Organization is determined by the Organizational Climate. A good organizational climate will result in high commitment to the organization and vice versa if the organizational climate is not good then the commitment to the organization is also low, (b) there is a significant positive relationship between work motivation and commitment to the organization with a correlation coefficient of ry. 2 = 0.789, the strength of the relationship "strong". The amount of contribution of work motivation to commitment to organization is 62.2% and the regression equation ? = 18.786 + 0.879X2. This means that the Commitment to the Organization is determined by Work Motivation. Good work motivation will result in a high commitment to the organization and vice versa if the work motivation is not good then the commitment to the organization is also low, and (c) there is a significant positive relationship between organizational climate and work motivation together with commitment to the organization with a coefficient correlation R = 0.792, the strength of the "strong" relationship. The amount of the contribution of Organizational Climate and Work Motivation together to Commitment to Organization is 62.8% and and the regression equation ? = 34.649 + 0.399X1 + 0.806X2. This means that commitment to the organization is determined by the organizational climate and work motivation together. If the Organizational Climate and Work Motivation together, contribute equally well, it will result in high Commitment to the Organization and vice versa if the Organizational Climate and Work Motivation together do not contribute well, Commitment to the Organization is also low